2019
DOI: 10.3389/fmicb.2019.01938
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Cronobacter Species Isolated From Four Infant Formula Production Factories in China

Abstract: The aim of this study was to investigate the prevalence and genotypic characteristics of Cronobacter isolated from powdered infant formula (PIF) manufacturing facilities and to identify a potential source of contamination. A total of 42 Cronobacter isolates (5%) were detected in 835 environmental samples collected during the surveillance study. These isolates included C . sakazakii ( n = 37), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…detection and identification of C. sakazakii in food samples as well as PMIF (Mashoufi et al, 2019). Recently; because of the employing strong surveillance and checking quality control of the manufactured and imported PMIF products, prevalence of C. sakazakii in PMIF has significantly been decreased (Lu & Matthews, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…detection and identification of C. sakazakii in food samples as well as PMIF (Mashoufi et al, 2019). Recently; because of the employing strong surveillance and checking quality control of the manufactured and imported PMIF products, prevalence of C. sakazakii in PMIF has significantly been decreased (Lu & Matthews, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We identified C. sakazakii in PMIF samples by real‐time PCR melting curve assay in our study; however, there are many researchers suggest SYBR green melting curve real‐time PCR with species‐specific primers a precise, sensitive and specific method for detection and identification of C. sakazakii in food samples as well as PMIF (Mashoufi et al., 2019). Recently; because of the employing strong surveillance and checking quality control of the manufactured and imported PMIF products, prevalence of C. sakazakii in PMIF has significantly been decreased (Lu & Matthews, 2019). However, different range of prevalence from 2.8% to 12.3% contamination rates of C. sakazakii was reported by researchers about PMIF samples (Henry, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A number of in‐depth studies of the distribution of Cronobacter in PIF manufacturing plants have been published and are highlighted in Table 2. The organism has been recovered from the ingredients as well as environmental samples (including roofs) from the spray‐drying, fluidized‐bed, and packing areas (Fei et al., 2015; Lu et al., 2019; Pei et al., 2019). Caprine (goat) milk powder is also used as an infant formula.…”
Section: Presence Of Cronobacter In Pif Infant Foods and Productionmentioning
confidence: 99%
“…Given the desiccation survival of Cronobacter , the dissemination of Cronobacter via air‐borne dust particles is very important to control in PIF production facilities. Dust particles in the air of a manufacturing plant can be a vector of Cronobacter dispersal, and could contaminate the final product during bagging and the final packing (Fang et al., 2015; Fei et al., 2015; Lu et al., 2019; Pei et al., 2019). Wu et al.…”
Section: Presence Of Cronobacter In Pif Infant Foods and Productionmentioning
confidence: 99%
“…Microbiological assessments of milk powder and PIF manufacturing environments and processes have shown that Cronobacter spp. may derive from extrinsic sources, notably dry ingredients, or intrinsically contaminated sites where specific strains may persist over long periods of time (29)(30)(31)(32)(33). Moreover, most strains examined to date have shown higher resistance to potentially lethal osmotic and dessication stresses than other human pathogen belonging to the family Enterobacteriaceae.…”
Section: Introductionmentioning
confidence: 99%